Krønike og kunst. Om den norrøne skjaldedigtningsom kilde til vikingetiden - Stavnem, Rolf (Historisk Tidsskrift, 2014)
Chronicle and Art. Old Norse Skaldic Poetry as a Source for Viking Age History A substantial part of skaldic poetry reports on important historical events and was composed by skalds contemporary with and close to those events. Apart from runic stones, other contemporary sources are scarce, so it is remarkable that skaldic poetry is largely neglected by Viking Age scholars. In an article from 2006 the Danish historian Niels Lund put forth a series of arguments as to why skaldic poetry is problematic as historical source material for the Viking Age. These arguments form the starting-point of the present article. For purposes of clarity they are divided into four sections: 1) the difficulties of interpreting skaldic poetry; 2) the problems regarding transmission; 3) the lack of precise dating criteria; and 4) the blurring of referentiality by the ambiguities of poetic language. Although none of these observations are wrong, they do not provide a full picture of the situation either. Some of the objections are met by the new edition of the complete skaldic corpus, the publication of which began after Lund’s article. However, it is also important to note that Old Norse society was in fact capable of oral transmission of a great quantity of information and that medieval historiographers regarded skaldic verse as an important source to the past. Furthermore, although it is impossible to date skaldic poetry with any certainty there is no convincing evidence that it was not, as a rule, composed in the Viking Age. On the contrary, preserved manuscripts present clear evidence that text handed down in metric form is older than the prose narratives. Finally, the source value of the skaldic corpus depends on the type of knowledge one seeks to establish on the basis of the material. For example, single stanzas reporting about specific events are more susceptible to doubt than the results of an investigation of a larger assemblage of stanzas concerning matters related to ideology or material culture.